The Psychoanalytic Listening and the Psychodramatic Techniques in a Group of Men Who Experienced Childhood Violence in Costa Rica - Zúñiga Araya, Rodrigo Alberto (2021)
Abstract. Objective. Systematize the contributions of the psychoanalytic clinic with psychodramatic and body techniques in a group of men who experienced violence in their childhood. Method. Systematization and analysis by theme categories, based on participant observation, written and audio recording, from the verbal and body speech of nine men in psychoanalytic group therapy by using psychodramatic techniques. Results. In conclusion, violence promotes an abusive relationship with the person himself, and the experience of pain is inscribed in the body as a possibility of expression. The group approach facilitated the reworking of psychic suffering through the body to recognize and verbalize emotions from the traumatic scene in an encounter of subjectivities.